STRATEGY FOR ENSURING OF INDONESIAN MIGRANT WORKERS (PMI) CHILDREN HAVE THE RIGHT TO A GOOD EDUCATION - Sudarmanto, Hery (International Journal of Social Science, 2022)
Indonesian migrant worker (PMI) issues have long been a source of endless public interest. The manner of parenting and education of PMI children is one of the issues that the program of the Indonesian government has not addressed. This study aims to analyze the problems faced by PMI children, relating to the fulfillment of their rights to proper care and education and to formulate strategies to overcome them. This study uses a qualitative approach with primary data collection using purposive sampling method in the provinces of East Java, West Java, West Nusa Tenggara and East Nusa Tenggara. The results showed that PMI's children's education problems could strategically be overcome by parenting and education in mutual cooperation by involving caregivers/educational actors from the informal, non-formal and formal education sectors. The government needs to continue to encourage collaboration and synergy of stakeholders involved in the care and education of PMI children from the government, private sector and community leaders/organizations. Problems that need to be addressed are also related to the provision of PMI children's data, so that they can be accessed easily in order to facilitate the planning of programs for handling PMI children's education problems.